Umbilical cord clamping in the early phases of the COVID-19 era – a systematic review and meta-analysis of reported practice and recommendations in guidelines - Johan Henrik Martin Berg; Li Thies-Lagergren; Jenny Svedenkrans; Jeremiah Samkutty; Sara Marie Larsson; Judith S. Mercer; Heike Rabe; Ola Andersson; Mehreen Zaigham (International Journal of Infectious Diseases, 2023)
Objectives: At the beginning of the COVID-19 pandemic, delayed umbilical cord clamping (CC) at birth may have been commonly discouraged despite a lack of convincing evidence of mother-to-neonate SARS-CoV-2 transmission. We aimed to systematically review guidelines, and reports of practice and to analyze associations between timing of CC and mother-to-neonate SARS-CoV-2 transmission during the early phases of the pandemic. Methods: Major databases were searched from December 1, 2019, to July 20, 2021. Inclusion: studies and guidelines describing CC practice in women with SARS-CoV-2 infection during pregnancy until 2 postnatal days, giving birth to live-born neonates. Exclusion: no extractable data. Two reviewers independently screened studies for eligibility and assessed study quality. Pooled prevalence rates were calculated. Results: Forty-eight studies (1476 neonates) and 40 guidelines were included. Delayed CC was recommended in 70.0% of the guidelines. Nevertheless, delayed CC was reported less often than early CC: 262/1476 (17.8%) vs 511/1476 (34.6%). Neonatal SARS-CoV-2 positivity rates were similar following delayed (1.2%) and early CC (1.3%). Most SARS-CoV-2 transmissions (93.3%) occurred in utero. Conclusion: Delayed CC did not seem to increase mother-to-neonate SARS-CoV-2 transmission. Due to its benefits, it should be encouraged even in births where the mother has a SARS-CoV-2 infection. Systematic review registration: Prospero CRD42020199500.